ALUR PIKIR GURU MATEMATIKA DALAM MEMBELAJARKAN SUATU KOMPETENSI DASAR DI KELAS VII SMP (Studi Kasus pada Guru Matematika SMP Negeri 1 Karanganyar) - Wulandari, Asih; Sujadi, Imam; Kusmayadi, Tri Atmojo (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objective of this research is to describe the mindset of Mathematics teachers in planning and implementation of learning process of a basic competency in Grade VII of State Junior High School 1 of Karanganyar. This research used the qualitative approach with the case study. The subjects of research were Mathematics teachers in Grade VII of State Junior High School 1 of Karanganyar, an experienced Mathematics teacher and a young Mathematics teacher. The data of research were collected through documentation, interview, and observation, and validated by using the source triangulation. The data that did not match were used as other findings. The data were analyzed by using the technique of data analysis from Miles and Huberman, by reducing the data, displaying the data, and drawing the conclusion. The results of this research are the mindset of teachers in the planning of the learning process begins with determining the basic competenciesÂ of each Core Competencies by examining the syllabus and describing it into indicators of competency achievement through Schoolâs Subject Teachers Forum, designing learning objectives, determining learning materials, and determining learning activities with scientific approaches. The designing of the assessment tools begins with describing the basic competencies of each core competency into indicator of competency achievement, determining assessment technique, and designing assessment tools. The mindset of teachers in implementation of the learning process refers to the Lesson Plan. It is shown by the use of scientific approaches, various learning methods that emphasize on the student-centered learning and authentic assessment.Keywords: Mindset of mathematics teacher, Lesson Plan,Â learning process, curriculum 2013.